Incidence and factors affecting endoparasitism in goats in Serdang, West Malaysia - Abdullah Sani, Rehana; Awang, I. P. R.; Sheikh Omar, Abdul Rahman (Persatuan Doktor Veterinar Malaysia, 1985)
The helminths found in the gastrointestinal tract of seventy-two goats necropsied from January 1977 to December 1983 were mainly Haemonchus contortus (67%), Moniezia expansa (51%) Oesophagostomum columbianum (42%) and Trichostrongylus colubriformis (38%). There was no correlation between age of the goats and worm burden for each of the helminth species. There was also no correlation between the prevalence of parasitism and rainfall values